THE EFFECT OF THE CHAIN WHISPER GAME ON CHILDREN’S RECEPTIVE LANGUAGE SKILLS - Herman Herman; Sulaiman Samad; Fitriani Dzulfadhilah (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
This study aims to investigate the effect of the chain whisper game on children’s receptive language skills. This study used a quasy-experimental design. The population in this study was all the students at Teratai Integrated Preschool in Makassar. With purposive sampling technique, the sample of this study was 12 students that were divided into 6 students in the experimental group and 6 students in the control group. The data was collected by conducting observations, tests, and documentation and then analyzed using descriptive statistical and nonparametric statistical methods. The results showed that the value of Asym (2-tailed) was 0.005 < 0.05, meaning that H1 was accepted and H0 was rejected and indicating that there were differences in receptive language skills between the experimental group and the control group. These results suggest that the chain whisper game has a significant effect on young children’s receptive language skills.